ANALYSIS OF STUDENTS' ANXIETY IN SPEAKING PERFORMANCE IN MUHAMMADIYAH UNIVERSITY OF MAKASSAR - Nurmuslimah Qadri; Nurdevi Bte Abdul; Maharida Maharida (FKIP Unismuh Makassar, 2023)
This study aims to determine the factors that cause students' anxiety in speaking performances and to determine the level of student anxiety in speaking performances in 3rd semester students, especially in speaking courses for the intermediate level at Muhammadiyah University of Makkassar.This research is a descriptive qualitative with a case study conducted on 8 students in semester 3. It consists of interviews and checklist observations. Each interview was used to find out the factors that cause students' anxiety in speaking performances. While, the observation checklist was carried out to determine the level of students‟ anxiety in speaking performance.The results of the study indicate that there are 2 factors that cause student anxiety, namely internal factors and external factors. Internal factors and external factors are very influential on students' anxiety on speaking performance. This can be seen from the results of data analysis at the student level in speaking performance. Therefore, it can be concluded that the factors that cause students‟ anxiety in speaking performance were internal and external factors. While at the level of students‟ anxiety there are three types, namely: low level of anxiety, medium level of anxiety and high level of anxiety.